Signaling pathways that activate hepatic stellate cells during liver fibrosis - Zhang, Youtian; Ren, Long; Tian, Yinting; Guo, Xiaohu; Wei, Fengxian; Zhang, Yawu (Frontiers in Medicine, 2024)
Liver fibrosis is a complex process driven by various factors and is a key feature of chronic liver diseases. Its essence is liver tissue remodeling caused by excessive accumulation of collagen and other extracellular matrix. Activation of hepatic stellate cells (HSCs), which are responsible for collagen production, plays a crucial role in promoting the progression of liver fibrosis. Abnormal expression of signaling pathways, such as the TGF-β/Smads pathway, contributes to HSCs activation. Recent studies have shed light on these pathways, providing valuable insights into the development of liver fibrosis. Here, we will review six signaling pathways such as TGF-β/Smads that have been studied more in recent years.